Tonotopic Organization in the Depth of Human Inferior Colliculus - Ress, David; Chandrasekaran, Bharath (Frontiers in Human Neuroscience, 2013)
Experiments in animal models indicate that inferior colliculus (IC), the primary auditory midbrain structure, represents sound frequency in a particular spatial organization, a tonotopy, that proceeds from dorsal and superficial to ventral and deeper tissue. Experiments are presented that use high-resolution, sparse-sampling functional magnetic resonance imaging (fMRI) at 3T to determine if tonotopic gradients can be reliably measured in human IC using high-resolution fMRI. Stimuli were sequences of band-pass filtered noise with different center frequencies, presented sequentially while fMRI data were collected. Four subjects performed an adaptive frequency-discrimination task throughout the experiment. Results show statistically significant tonotopic gradients within both ICs of all subjects. Frequency gradients as a function of depth were measured using surface-based analysis methods that make virtual penetrations into the IC tissue. This organization was evident over substantial portions of the IC, at locations that are consistent with the expected location of the central nucleus of IC. The results confirm a laminar tonotopy in the human IC at 3T, but with a heterogeneous, patchy character. The success of these surface-based analysis methods will enable more detailed non-invasive explorations of the functional architecture of other subcortical human auditory structures that have complex, laminar organization